(untitled) (Quinto Sol, 2024)
This dossier constitutes a sample of research that has been carried out for several years on the problem of social consensus that has emerged under dictatorial state regimes. In this publication, the compiled articles focus on the analysis of the consensus related to the last military dictatorship in Argentina (1976-1983) with the objective of investigating the generation processes, identifying the specific strategies and their persistence or their change over time. over time. Specifically, they wonder about the way in which, through communication and culture, the self-proclaimed “National Reorganization Process” attempted to provoke the population’s adherence to its political project.